2015
DOI: 10.1128/aac.01457-15
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Single versus Combination Antibiotic Prophylaxis for Infections after Transrectal Prostate Biopsy

Abstract: An increase in fluoroquinolone resistance and transrectal ultrasound-guided prostate (TRUS) biopsy infections has prompted the need for alternative effective antibiotic prophylaxis. We aimed to compare ciprofloxacin and other single-agent therapies to combination therapy for efficacy and adverse effects. Men who underwent a TRUS biopsy within the VA Boston health care system with documented receipt of prophylactic antibiotics periprocedure were eligible for inclusion. Postprocedure infections within 30 days we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 10 publications
0
5
1
Order By: Relevance
“…This can be easily understood because broad spectrum antibiotics were used often during intensive surgery. These results regarding patient characteristics are not consistent with those of other studies, 16 24 and some considerations should be pondered to determine whether or not this risk factor is important prior to TRUSPB. Because western and European countries usually follow guidelines recommending single-dose prophylactic antibiotics in most surgeries, recent surgical history may not be a risk factor in these countries.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…This can be easily understood because broad spectrum antibiotics were used often during intensive surgery. These results regarding patient characteristics are not consistent with those of other studies, 16 24 and some considerations should be pondered to determine whether or not this risk factor is important prior to TRUSPB. Because western and European countries usually follow guidelines recommending single-dose prophylactic antibiotics in most surgeries, recent surgical history may not be a risk factor in these countries.…”
Section: Discussioncontrasting
confidence: 93%
“…Marino et al 24 reported that single agents, such as ciprofloxacin, ceftriaxone, and gentamicin, alone are less effective than a combination regimen as prophylaxis for TRUSPB. In some studies, researchers argued that more intensive antibiotic regimens were needed to reduce the rate of complications.…”
Section: Discussionmentioning
confidence: 99%
“…in their study, Choi et al (19) Reported that 39 of 1195 (3.1%) Korean patients were infected after biopsy. Also, Marino et al (20) did a three-year study in the United States and declared that 25 of 455 (5.49%) patients reported UTI. Besides, Kandemir et al (21) In Turkey in 2016 stated a rate of 6.91% for UTI among 2215 patients underwent TRUS biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…Combinations of antibiotics are applied for up to 50% of patient cases in the treatment of severe surgical site infections, bacteremia, pneumonia, or septic shock [ 1 4 ]. Antibiotic combinations are also frequently prescribed as prophylactic treatments to prevent post-operation-related infections [ 5 , 6 ] and in the treatment of complicated chronic infections [ 7 9 ]. The rationale for combination therapy compared to monotherapy is 3-fold: (i) a broadened activity range by combining the different modes of action, pharmacodynamics, and pharmacokinetics of different antibiotics, (ii) stronger treatment effect, and (iii) reduced risk of resistance evolution.…”
Section: Introductionmentioning
confidence: 99%